PERILAKU KONSUMTIF DAN GAYA HIDUP PENGGEMAR SEPEDA FIXED GEAR DI KOTA DENPASAR - Syukur, M.; Sastri Mahadewi, Ni Made Anggita; Agung Krisna Aditya, I Gusti Ngurah (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
A consumption society is a group that is constantly engaged in consumption activities. However, consumption in this context has evolved from simply fulfilling basic human needs to a lifestyle. According to Baudrillard, the consumption pattern of postmodern society is characterized by a shift in orientation from life needs to lifestyle expressions. This study aims to analyze the consumptive behavior and lifestyle of fixed gear bicycle enthusiasts in Denpasar City using an explanatory descriptive qualitative approach and Jean P. Baudrillard's theory of consumption society. The results showed that fixed gear bikes are not only a means of transportation, but also a symbol of identity expression and lifestyle. The consumption of symbols gives birth to a society of spectacle where symbolic exchange creates social distance and differentiates individuals within the community. Preferences for bicycles, brands, styles, and associated values shape identities and groups within the community.